Footloose Multinationals in Belgium - Ilke Van Beveren (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2006)
Using firm level panel data for the years 1996-2001, covering all sectors of the economy, the impact of multinational ownership on the exit decisions of firms located in Belgium is estimated. In the analysis, I clearly distinguish for nationality of ownership, allowing for possible differences between firms that are foreign-owned and multinationals rooted in the domestic economy. Controlling for various firm- and industry-specific factors, it is found that while foreign multinationals are more likely to shut down operations compared to national firms in both manufacturing and service sectors, domestic multinationals only exhibit significantly higher exit rates in the manufacturing industries. The analysis has important policy implications, especially in tfirms of the desirability of the large impact of multinational firms on employment and output generation in Belgium.
Keywords: D21; F23; L20; L25; 330; exit; survival; multinational firms; nationality of ownership; Multinationales Unternehmen; Unternehmen; Panel; Belgien; Marktaustritt